A study of the adaptability of certain forestry species to central Kansas planting - Houser, Frederick (My University, 1907)
Introduction: Were it necessary for one to test each species before planting his trees in order to find out which species are particularly adapted to his locality it would require a great deal of time as well as expense before he would be able to decide. During this time had he known which species thrives best, his forest or wood lot, as the case may be would be under considerable headway. Experimenting as a side line is a good thing, but when it is the desire to obtain species for immediate purpose in this way it is not profitable. One may not know which species are adapted to his locality but he should observe species that are hardy and rapid growers in a locality whose conditions are similar to those of his own locality.
Citation: Houser, Frederick. A study of the adaptability of certain forestry species to central Kansas planting. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Native Species; Flora; Kansas Plants; Theses